HAK PENGASUHAN ANAK DI BAWAH UMUR SEBAGAI AKIBAT PERCERAIAN - Agung Pratama; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2023)
The Cases of disputes over child custody (hadhanah) due to divorce are common in society. For underage children, Article 105 (1) KHI provide hadhanah to their mothers. However, court may determine otherwise through a mediation. The research’s problem: what are the provisions regarding hadhanah as result of divorce according to the Marriage Law, and is the Decision of PA Sukadana No: 1057/Pdt.G/2019/PA. Sdn, is in accordance with marriage laws. The research conducted in normative and descriptive analytical legal research, using secondary data obtain through literature studies. The data is analyzed qualitatively and conclusions are drawn using deductive understanding. The conclusion is that the Marriage Law does not definitively regulate the hadhanah. Hadhanah is regulated in Article 105 paragraph (1) KHI, namely